The modelling of balance between energy efficiency and economy and simulation analysis in electric gas production technology. (5th October 2022) - Wang, Jiajun; Wang, Yahui; Qi, Wenjie
The simulation optimisation analysis on electric gas production technology (power to gas, P2G) was conducted by exergy analysis method. The energy efficiency equation of electrolysis water and methanation in P2G was established. The net present value (NPV) method was used to analyse the economy of P2G and the economy equation of P2G is established. The balance between economy and energy efficiency of the system was adjusted using the optimisation weight coefficient. The optimisation model of balance between energy efficiency and economy in P2G and its constraint equation are established, and the optimisation simulation analysis was carried out by combining Lagrange relaxation and branch-and-bound method. The analysis results have shown that the profit of the P2G is affected by the efficiency of electrolysis water and methanation as well as equipment investment. By optimising the P2G process and investing the equipment reasonably, the maximum economic benefit of the P2G system can be obtained.